Design and analysis a new materials of gasket pipping using waste rubber tyres and coconut coir fibre - Md Palil, Md Dan; Yu, Aaron Lung (Penerbit Universiti Teknikal Malaysia Melaka, 2012)
Waste tyres are a tremendous problem throughout the world. The tyre is designed to be tough and hardwearing, once they are no good as tyres they are difficult to cut up, hard to store or transport and of little value to anyone. With the growth of the industrial sector, gasket will become one of the most important things in the piping industrial. By converting waste tyre into gasket, it gives advantages to both parties. Embedded with coconut coir fibre is to increase the mechanical strength of the waste rubber material. The fabrication of the gasket will involved internal mixing which is to mix up the waste tires with the coconut coir fibre and hot pressing is to press or sinter the material into gasket. The testing involved in this project is Tensile Test, Hardness Test, Absorption Test and last is Thickness Swelling Test. The result and data collected will be analysing by using graphs. Apart from that, software like CATIA and ANSYS will be used to in providing solid modelling and analysis on gasket and mould. After analysing all the data, this project can be concluded that coir fibre is a very good reinforcement by increase the mechanical properties in polymer but at certain amount it can change the properties of the composites. From this project, the best composition is 85% waste rubber+5% coir fibre+10% Polypropylene.